2020
DOI: 10.3390/agronomy10111711
|View full text |Cite
|
Sign up to set email alerts
|

Response of Drip Irrigation and Fertigation on Cumin Yield, Quality, and Water-Use Efficiency Grown under Arid Climatic Conditions

Abstract: A three-year field experiment was conducted at the Agricultural Research Station of Mandor, Jodhpur, Rajasthan, under arid climatic conditions in the rabi season of 2016–2019 with the objectives of evaluating the effect of drip irrigation and fertigation levels on cumin plant growth, yield, oil content, water-use efficiency, and water productivity. The pooled data revealed that the drip irrigation at 0.6 cumulative pan evaporation (CPE) recorded significantly higher plant height (31.4 cm), umbels plant−1 (50.4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Mirhosseini et al, (2011) in their results, show that the number of umbellates per umbel was between 3.48 and 4.96 and reported the difference between the populations in terms of the number of umbellates per umbel. Also, Mehriya et al, (2020) in their study, reported the number of umbellates inside umbels was between 4.60 and 5.07.…”
Section: Resultsmentioning
confidence: 88%
See 3 more Smart Citations
“…Mirhosseini et al, (2011) in their results, show that the number of umbellates per umbel was between 3.48 and 4.96 and reported the difference between the populations in terms of the number of umbellates per umbel. Also, Mehriya et al, (2020) in their study, reported the number of umbellates inside umbels was between 4.60 and 5.07.…”
Section: Resultsmentioning
confidence: 88%
“…The number of seeds per umbellate for the population of Afghanistan with 4.53 and 4.56 seeds is the lowest in 2020 and 2021, respectively (Table 4). Mehriya et al, (2020). In their study in India, they reported the number of seeds per umbellate to be 4.70 to 5.34.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…Hence, water saving technologies in agriculture can be broadly classified into three: water saving crop technologies, water saving and yield enhancing irrigation technologies; and, yield improving crop technolo-gies (Singh et al, 2013;Kumar and Palanisami, 2011;Palanisami et al, 2011;El-Habbasha et al 2014;Zafar et al, 2020). Many past researchers have reported high water use efficiency and crop yield under drip method of irrigation as compared to conventional irrigation throughout the globe (Singh, et al, 2013;Kumar and Palanisami, 2011;Narayanamoorthy, 2012;Abdelraouf et al, 2020;Barkunan et al, 2019;Uddian and Dhar, 2020;Zafar et al, 2020;Mehriya et al, 2020). In drip irrigation, the volume of wetted soil at a particular water application is controlled by the volume of water added, dripper discharge rate and the water content in the soil.…”
mentioning
confidence: 99%